LAGU-LAGU TEMBANG SUNDA CIGAWIRAN - Oman Resmana (Paraguna, 2016)
Tembang Sunda  Cigiawiran  is a  kind  of tembang presented by sekar (vocals)  without gending accompaniment.   The form of Ruumpaka used in this   tembang  is pupuh 17. I holds an important   role as a  medium of Islamic siar dissemination especially  in Cigawir Village Sela Awi  District Garut Regency. A Cigawiran singer must be sensitive towards laras  that is delivered.    Besides  she  must  have   a  wide  range  of voice  due   to  the coverage  of varies  tone area.